Application of 3P Sampling System over fixed plots in a Nothofagus pumilio forest in Chubut Province - Carabelli, Francisco Andrés (Bosque (Valdivia), 1993)
The 3P Sampling -Probability Proportional to Prediction- combined with a fixed plot sampling which used a simple systematic design, was applied experimentally. A Silvicultural Management Schedule for lenga (Nothofagus pumilio (Poepp. et Endl.) Krasser was used at Lago Fontana area, Chubut Province. The main object of the study was to apply a mixed sampling technique that would project the major advantages of both sampling systems in small and medium size inventories. The results indícate that it is technically feasible and economically convenient to implement this technique, while more applications are essential for its consolidation.